Arbeid van vrouwen in Limburg in de twintigste eeuw: een stille revolutie - Knotter, Ad (TSEG - The Low Countries Journal of Social and Economic History, 2020)
Female labour force participation declined in Limburg from a relatively high level at the start of the twentieth century to a relatively low level at the end of that century. In this article this “silent revolution” is analysed by focussing on the development of women’s labour in agriculture, in the South Limburg mining district, and in the Maastricht glass and pottery industries. The high level of female labour force participation was, firstly, caused by a high labour input of women in small farming predominating in Limburg agriculture well into the 1950s, secondly, by the many women, both married and unmarried, employed in the Maastricht glass  and pottery works. In the mining districts, by contrast, women’s paid labour was almost absent (apart from employment of young, unmarried women in the clothing industry). The relative decline of female labour in the Province of Limburg is foremost a consequence of the growth of mining relative to agriculture. But in agriculture and the Maastricht industries female labour declined as well, due to the exodus of young women out of agriculture in the first, and of changes in production and employers’ policies in the second case.